Sexual assault and sexual harassment in the U.S. military. - Morral, Andrew R.; Gore, Kristie L.; Schell, Terrie L. (Research report (Rand Corporation), 2015)
"In early 2014, the Department of Defense Sexual Assault Prevention and Response Office asked the RAND National Defense Research Institute to conduct an independent assessment of the rates of sexual assault, sexual harassment, and gender discrimination in the military -- an assessment last conducted in 2012 by the Department of Defense using the Workplace and Gender Relations Survey of Active Duty Members. The resulting RAND Military Workplace Study invited close to 560,000 U.S. service members to participate in a survey fielded in August and September of 2014. This volume presents results from this survey for active- and reserve-component service members in the Army, Navy, Air Force, and Marine Corps. It includes estimates of the number of service members who experienced sexual assault, sexual harassment, or gender discrimination in the past year, as well as detailed information about the characteristics of those incidents, decisions to report, and experiences with response and legal systems for both male and female service members. It also describes service members' beliefs and attitudes about these problems."--Website